Analisis Faktor yang Mempengaruhi Motivasi Kerja Pegawai BPKPD Kota Pariaman - Yulina Eliza; Yenni Resvianti; Yudha Eka Saputra; Yuharmen Yuharmen (Target : Jurnal Manajemen Bisnis, 2022)
This study aims to see the effect of (1) work placement on the work motivation of BPKPD Kota Pariaman employees, (2) work ability on the work motivation of BPKPD Kota Pariaman employees, (3) career development on the work motivation of BPKPD Kota Pariaman employees, (4) promotion on the work motivation of BPKPD Kota Pariaman employees and (5) work placement, work ability, career development and promotion simultaneously on the work motivation of BPKPD Kota Pariaman employees. The sample is all employees at BPKPD Kota Pariaman as many as 60 people. Data processing uses Multiple Linear Regression using the SPSS 25 application program. The results of this study indicate that (1) Work placement has a significant positive effect on work motivation (2) Work ability has a positive influence on work motivation (3) Career development has a positive influence positive effect on employee motivation (4) Promotion has a positive effect on work motivation and (5) Work placement, work ability, career development and promotion simultaneously affect employee motivation in BPKPD Kota Pariaman.